Can cold-tolerant hybrids be created by crossing cold-tolerant parental lines? - Kolomatska, Valeriia; Relina, Liana; Syvenko, Valentyna; Leonova, Nina (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(3): 212–217